Scrub Typhus with Partial Superior Orbital Fissure Syndrome - Sanyam K. Mahajan; Vinay Gupta; Sudhir Sharma; Suresh Thakur (Delhi Journal of Ophthalmology)
We report a case of a 33 year old woman suffering from scrub typhus who presented with binocular horizontal diplopia. Magnatic Resonance Imaging of Brain showed thickening and enhancement of the lateral wall of cavernous sinus, extending to involve orbital apex. She improved after treatment with doxycycline. Various ophthalmological manifestations of scrub typhus have also been reviewed.